Correlation between number of mature eggs retrieved and live birth rate in IVF treatment - Rana, Lekshmy; Bavishi, Himanshu; Bavishi, Falguni (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: There is a strong association between the number of eggs and clinical pregnancy rates. But a few studies have shown conflicting results. Aim was to determine the relation between number of mature eggs retrieved and live birthrate in one complete IVF cycle (fresh and all frozen transfers included) and hence determine the optimum number of oocytes. Private IVF centre doing around 2000 cycles per year. Methods: Retrospective analysis of 1140 infertile women between 20 and 45 years who underwent self-stimulation IVf in our centre. Cumulativelive birth rate in one complete IVF cycle. Secondary outcome was the number of cases of moderate and severe OHSS. Results: Maximum LBR in patients where 10-15 egg were retrieved in fresh embryo transfer and cumulative LBR was maximum when more than 15 eggs were retrieved. No case of severe OHSS and one case of moderate OHSS in the group where more than 15 eggs were retrieved. Conclusions: The percentage of live birth increases with increasing number of mature eggs in IVF treatment. The incidence of OHSS was negligible.